A study of the health information, interests, and practices of high school students in the City of Davao - Occena, Efigenia C. 1914- (1954)
A survey of the health information, interests, and practices of high school students in the City of Davao was conducted in this study. It is hoped that the results of this study may, in some way, bring about a new approach to health instruction in secondary schools, thereby making the school health education program effective in improving personal and community health.